Assessing children's willingness to try new foods: Validation of a Portuguese version of the child's food neophobia scale for parents of young children. (January 2018) - Gomes, Ana Isabel; Barros, Luisa; Pereira, Ana Isabel; Roberto, Magda Sofia; Mendonça, Mariana
Highlights: A Portuguese version of the Child's Food Neophobia Scale was studied. A two-factor solution ( Food Neophobia and Food Neophilia ) achieved the best fit data. Invariance analysis showed the same structure only for children's age groups. Good reliability results and concurrent/discriminant validity were attained. Abstract: Because of the well-established effect of food neophobia on children's variety of food consumption, the availability of valid measures of food neophobia in young children is necessary. We studied a Portuguese version of the Child's Food Neophobia Scale (CFNS), assessing its validity and reliability. The CFNS was completed by 388 parents of 2-to 6-year-old children. Construct validity was examined through an exploratory factorial analysis and a confirmatory factorial analysis. Measurement invariance (child's age and sex) and reliability analysis were examined. Correlational analyses between the CFNS and children's eating habits, food preferences and temperament dimensions were run. The results support a two-factor solution, suggesting two opposite dimensions: Food Neophobia and Food Neophilia . Invariance analysis showed the same structure for both age groups (2- to 4- vs. 5- to 6-year old), although only partial metric invariance across sex groups was attained. For both Food Neophobia and Food Neophilia subscales, good internal consistency and excellent test–retest reliability were achieved, as well as a moderate negative association between the two groups of items. Higher scores in Food Neophobia and lower scores in Food Neophilia were significantly correlated with a more inhibited temperament, lower preference for healthy foods, acceptance of fewer foods, less frequent consumption of healthy foods, and consumption of a smaller variety of fruits, vegetables and legumes. Children's unhealthy food intake was not associated with both CNFS subscales. Our preliminary findings support the adequacy of this version of CFNS for the Portuguese population. Further studies are needed to confirm the two-dimensional structure of the scale and explore the implications of this structure. Assessing children's willingness to try new foods: validation of a Portuguese version of the Child's Food Neophobia Scale for parents of young children.